Nurturing Ecological Citizenship: Integrating Panglima Laot Values into School Co-Curricular Programs in Aceh - Mudassir Mudassir; Helda Kusuma Wardani; Andistya Ravelina Putri; Dhestya Praba Pramudita; Hana Andriningrum (Winaya Inspirasi Nusantara Foundation, 2027)
The integration of local wisdom into formal education has become increasingly important in addressing challenges related to cultural preservation, character development, and environmental sustainability. In Aceh, Panglima Laot is a traditional maritime institution that embodies values of leadership, cooperation, responsibility, deliberation, social justice, and environmental stewardship. However, despite its important role in Acehnese society, the educational potential of Panglima Laot has not been systematically integrated into elementary school co-curricular programs. This study aims to explore how Panglima Laot values can be integrated into elementary school co-curricular programs and to examine their contribution to strengthening students’ character and environmental awareness. A qualitative case study approach was employed in several coastal elementary schools in Banda Aceh. Data were collected through semi-structured interviews with Panglima Laot leaders, school principals, teachers, students, and parents, complemented by observations, focus group discussions, and document analysis. Data were analyzed using the interactive model of Nurmala, V., et al., (2025). The findings reveal that Panglima Laot values can be effectively integrated into co-curricular activities through beach clean-up campaigns, mangrove planting projects, maritime cultural literacy programs, environmental conservation initiatives, and community-based learning activities. The implementation of these activities contributed to the development of students’ responsibility, cooperation, environmental awareness, and appreciation of local cultural heritage. The study also found that collaboration between schools and community stakeholders strengthened the effectiveness of local wisdom-based learning. The study implies that integrating Panglima Laot values into co-curricular programs provides an innovative model for local wisdom-based education that supports character education, environmental sustainability, and the preservation of Acehnese maritime culture. The findings offer practical insights for educators, curriculum developers, and policymakers seeking to incorporate indigenous knowledge and local wisdom into elementary school education.